Radiation Technology for Polymers, Second Edition - Drobny (CRC Press, 2012)
The first edition of Radiation Technology for Polymers set the standard as a valuable, time-saving resource offering systematic fundamental information about industrial radiation technologies. Raising the bar even further, Radiation Technology for Polymers, Second Edition explores emerging applications of ultraviolet (UV) and electron beam (EB) radiation to polymer processing, detailing significant changes in the field since the first publication